Implementasi Layout Desain Grafis pada Konten Fanpage Gameqoo di Diarium Internal Telkom - aulia berliani; Yenni Yuniati (UNISBA Press, 2022)
Abstract. PT Telkom Indonesia (Persero) Tbk (Telkom) is a State Owned Enterprise State-owned enterprises (BUMN) engaged in information technology services and communication (ICT) and telecommunications networks in Indonesia. In an attempt transformed into a digital telecommunication company, TelkomGroup implement the company's business and operational strategies that customer-oriented (customer-oriented). The transformation will make the TelkomGroup organization more lean (lean) and agile (agile) in adapting to changes in the telecommunications industry which is going very fast. For 6 months undergoing a certified internship with an independent campus and PT Telkom Indonesia as a partner, is a challenge for the participants to help partners (companies/startups/communities) to work on graphic design needs. Participants will be equipped with the ability Design Testing, Design Evaluation, Design UI/UX and others. Besides Therefore, participants will be given hands-on experience in a team to create several marketing campaigns that require design needs. This program has a mission, namely to improve work abilities/skills and job readiness for participants by equipping (soft skills, graphic design, UI/UX, layout design, problem analysis, etc.), provide experience as a graphic designer and connect participants to partners company for job opportunities. Participants are given the opportunity to learn about workflows, job desks and others for 2 weeks, then the remaining 22 weeks are used for real project work on partners. Abstrak. PT Telkom I ndonesia (Persero) Tbk (Telkom) adalah Badan Usaha Milik Negara (BUMN) yang bergerak di bidang jasa layanan teknologi informasi dan komunikasi (TIK)dan jaringan telekomunikasi di Indonesia. Dalam upaya bertransformasi menjadi digital telecommunication company, TelkomGroup mengimplementasikan strategi bisnis dan operasional perusahaan yang berorientasi kepada pelanggan (customer-oriented). Transformasi tersebut akan membuat organisasi TelkomGroup menjadi lebih lean (ramping) dan agile (lincah) dalam beradaptasi dengan perubahan industri telekomunikasi yang berlangsung sangat cepat. Selama 6 bulan menjalani magang bersertifikat bersama kampus merdeka dan PT Telkom Indonesia sebagai mitra, merupakan tantangan tersendiri bagi para peserta untuk membantu mitra (perusahaan/startup/komunitas) untuk mengerjakan kebutuhan design grafis. Peserta akan dilengkapi dengan kemampuan Desain Testing, Desain Evaluation, Desain UI/UX serta yang lain-lain. Selain itu, peserta akan diberikan pengalaman langsung didalam sebuah tim untuk membuat beberapa campaign marketing yang memerlukan kebutuhan desain. Program ini memiliki misi yaitu meningkatkan kemampuan kerja/skill dan kesiapan kerja bagi peserta dengan membekali (soft skill, desain grafis, desain UI/UX, desain layout, problem analysis dan lain-lain), memberikan pengalaman sebagai desainer grafis dan menghubungkan peserta ke mitra perusahaan untuk peluang kerja. Peserta diberikan kesempatan untuk belajar mengenai workflow, jobdesk dan lain-lain selama 2 minggu, kemudian sisa 22 minggu digunakan untuk pengerjaan proyek nyata pada mitra.